GELIFLUCTION IN THE ALPINE PERIGLACIAL ENVIRONMENT OF THE TIANSHAN MOUNTAINS, CHINA - LIU, GN; XIONG, HG; CUI, ZJ (permafrost and periglacial processes, 1995)
Gelifluction in the periglacial zone of the Tianshan Mountains occurs at 2500-3600 m above sea level on north-facing slopes. Abundant groundwater, fine grained sediments and slopes 10 degrees-30 degrees favour gelifluction. Most gelifluction forms are lobate, a few are tongue-shaped. The mean surface rate of movement is 11.14 cm/a; the front advancing rate is 1.86 cm/a. The moving rate in the middle part is greater than at the sides of gelifluction lobes, the mean rates being 3.1 cm/a and 0.86 cm/a, respectively. Geography, Physical Geology SCI(E) 2 NOTE 3 265-271 6